2016
DOI: 10.1016/j.bbmt.2015.08.034
|View full text |Cite
|
Sign up to set email alerts
|

Single-Agent Post-Transplantation Cyclophosphamide as Graft-versus-Host Disease Prophylaxis after Human Leukocyte Antigen–Matched Related Bone Marrow Transplantation for Pediatric and Young Adult Patients with Hematologic Malignancies

Abstract: High dose cyclophosphamide given after HLA-matched related and unrelated allogeneic bone marrow transplantation (BMT) for patients with hematologic malignancies is effective single agent graft-versus-host disease (GVHD) prophylaxis in adults. Data describing outcomes for pediatric and young adult patients has not been reported. Between the years 2007-2013, 29 pediatric and young adult patients age ≤ 21 years of age treated at our institution for high-risk hematologic malignancies underwent myeloablative HLA-ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 56 publications
0
31
0
Order By: Relevance
“…However, limiting the duration of immunosuppression has been associated in many platforms with an increased risk of severe aGVHD and cGVHD. We have previously shown that high-dose PTCy is an effective single-agent prophylactic strategy after HLA-matched BMT [1013] and seems to reduce severe aGVHD and cGVHD without concomitant decreases in the incidence of grade II aGVHD. Similar to recent studies in haplo BMT with PTCy [9] and umbilical cord transplantation [30] we demonstrate that grade II aGVHD is associated with significantly improved OS and PFS in HLA-matched BMT with PTCy.…”
Section: Discussionmentioning
confidence: 99%
“…However, limiting the duration of immunosuppression has been associated in many platforms with an increased risk of severe aGVHD and cGVHD. We have previously shown that high-dose PTCy is an effective single-agent prophylactic strategy after HLA-matched BMT [1013] and seems to reduce severe aGVHD and cGVHD without concomitant decreases in the incidence of grade II aGVHD. Similar to recent studies in haplo BMT with PTCy [9] and umbilical cord transplantation [30] we demonstrate that grade II aGVHD is associated with significantly improved OS and PFS in HLA-matched BMT with PTCy.…”
Section: Discussionmentioning
confidence: 99%
“…This procedure has been shown to eliminate proliferative allo-reactive T cells, while preserving resting, non-reactive T cells. Infection risk also decreases through preservation of virus-specific T cells [40]. Posttransplant Cy was reported to be used in allo-transplants in adult SCD patients and HLA-matched sibling donors by Bolanos-Meade et al [41].…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of acute GVHD was low at 22.2%, with a low incidence of chronic GVHD of 22.7%. PTCY is increasingly used either alone or in combination with calcineurin inhibitors or sirolimus to reduce the incidence of GVHD after sibling donor transplants [18][19][20][21][22][23][24][25][26]. The combination of PTCY with calcineurin inhibitors has been associated with low rates of acute (17% to 40%) and, importantly, chronic GVHD (7% to 16%), but data on its single use have shown very conflicting rates of GVHD.…”
Section: Discussionmentioning
confidence: 99%
“…Although the above studies have described GVHD rates with PTCY in the setting of PBSCs as the graft source, the use of BM as the graft source while using PTCY has also shown conflicting data. Jacoby et al [25] in a study of 29 pediatric and young adult patients undergoing myeloablative HLAmatched related T cell-replete BM transplantation showed a 0% incidence of acute and chronic GVHD in those receiving PTCY (n = 11) compared with 27% and 5%, respectively, with the use of calcineurin inhibitor-based GVHD prophylaxis. However, Kanakry et al [26] in a multi-institutional study of 92 patients having allogeneic BM transplantation using myeloablative busulfan and fludarabine conditioning with PTCY as the single-agent GVHD prophylaxis showed acute and chronic GVHD rates of 51% and 14%, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation